Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:1. The impact of social engineering on cybersecurity risks in banks in the city of Riyadh in the Kingdom of Saudi ArabiaMr. Abdullelah Saeed Al Mohayya, Ms. Arwa Ahmed Makeen2. The impact of the university education and knowledge transfer index on the global competitiveness of the United Arab Emirates from the perspective of quality employeesDr. Shawk Hasan Mahdi3. Evaluating the impact of artificial intelligence applications on accelerating the project life cycle  and increasing its flexibility: A comparative study of agile and traditional management methodologiesDr. Anwar Mohammed Gismallah Mohammed4. The role of automation in improving the performance of human resources: A field study on the employees of Al-Habib Real Estate CompanyMs. Afrah Ahmed Mahdami5. The financial sector in the Kingdom of Saudi Arabia’s Vision 2030: Evaluation and achievementsDr. Emad Adnan Matyori6. Economic analysis of the provision of industrial and manufacturing services in the Kingdom of Saudi Arab 2024Dr. Sadiq Ali Mubarak Al-Shuwaikhat, Dr. Haya Ibrahim Abdulrahman Al Tuwaym, Dr. Sara Saad Al-Dawsari7. Measuring the impact of the economic balance goals on the economic growth of the Iraqi economy for the period  (1990-2023)Asst-Prof. Sikna  Jahya Faraj8. The nexus between Public Investment Fund Sports Revenue and economic development in Saudi ArabiaMs. Furqan Mahfouz Ali Almdoudi, Dr. Somaiyah Fahad Alalmai
Keywords: Journal of Economic, Administrative and Legal Sciences